2018
DOI: 10.1053/j.semperi.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Modulators of inflammation in Bronchopulmonary Dysplasia

Abstract: Over 50 years after its first description, Bronchopulmonary Dysplasia (BPD) remains a devastating pulmonary complication in preterm infants with respiratory failure and develops in 30–50% of infants less than 1000-gram birth weight. It is thought to involve ventilator- and oxygen-induced damage to an immature lung that results in an inflammatory response and ends in aberrant lung development with dysregulated angiogenesis and alveolarization. Significant morbidity and mortality are associated with this most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 178 publications
(173 reference statements)
0
68
0
Order By: Relevance
“…Aerosol delivery of medications to preterm infants, while they are managed with NIV, has been attempted for decades with limited success [11,27]. Eventually, an efficient method of non-invasive aerosol delivery should enable the safe prevention and treatment of lung conditions associated to preterm birth, such as RDS and BPD, by the topical administration of nebulized surfactant, anti-inflammatory drugs, and other molecules that promote lung development [27,28]. Unfortunately, lung deposition in preterm infants is very low, and is fundamentally affected by the low lung volumes and fast breathing rates of preterm babies, the nebulizer type, the diluting effect of the bias flow during NIV and the NIV ventilation circuit, including the NIV interface [11,29].…”
Section: Discussionmentioning
confidence: 99%
“…Aerosol delivery of medications to preterm infants, while they are managed with NIV, has been attempted for decades with limited success [11,27]. Eventually, an efficient method of non-invasive aerosol delivery should enable the safe prevention and treatment of lung conditions associated to preterm birth, such as RDS and BPD, by the topical administration of nebulized surfactant, anti-inflammatory drugs, and other molecules that promote lung development [27,28]. Unfortunately, lung deposition in preterm infants is very low, and is fundamentally affected by the low lung volumes and fast breathing rates of preterm babies, the nebulizer type, the diluting effect of the bias flow during NIV and the NIV ventilation circuit, including the NIV interface [11,29].…”
Section: Discussionmentioning
confidence: 99%
“…The study selection process and exclusion criteria are described in Fig 1. Of the 128 studies identified initially, 120 were excluded based on review of the title, abstract or full text. The reasons for excluding 17 studies [33,34,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] after full-text review, are provided in Fig 1. The remaining eight studies met the inclusion criteria and were included in the meta-analysis [35,37,38,40,41,43,61,62].…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…In ammation is the common pathway that leads to the phenotype of the disease and further compromises the structure and function of the patient's respiratory system (24). However, pro-in ammatory cascades are complex and redundant, involving numerous different cell types and molecular pathways triggered by either cell-to-cell interactions or paracrine signals from damaged tissues (34). Therefore, MSC transplantation emerges as a promising therapy investigated in a recently reported phase I clinical trial (21).…”
Section: Discussionmentioning
confidence: 99%